A new Jurassic carnivorous cockroach (Insecta, Blattaria, Raphidiomimidae) from the Inner Mongolia in China - Liang, Jun-Hui; Vršansku, Peter; Ren, Dong; Shih, Chungkun (Zootaxa, 2009)
Fortiblatta cuspicolor gen. et sp. nov., a carnivorous cockroach of the family Raphidiomimidae Vishniakova, 1973, is described from the Middle Jurassic Jiulongshan Formation of Daohugou, Eastern Inner Mongolia, China. Fifty complete specimens reveal morphological details, including prognathous head and distinct, protected eyes. Internalized outer valves of female ovipositor suggest that their reproduction was advanced, with eggs laid in conglomerates. The wide abdominal segments, long palps, and wing characteristics support their origin from representatives of the family Caloblattinidae. The asymmetrical long wings (different shape, length, width and number of veins in a pair of wings of the same individual) and low coefficient of venation variability of forewing (7.70) indicate the new species was active but not excellent flyer.